Neonatal nephron loss during active nephrogenesis results in altered expression of renal developmental genes and markers of kidney injury - Raming, Roman; Cordasic, Nada; Kirchner, Philipp; Ekici, Arif Bülent; Fahlbusch, Fabian; Wölfle, Joachim; Hilgers, Karl Friedrich; Hartner, Andrea; Menendez-Castro, Carlos (Physiological Genomics, 2021)
Preterm neonates are at a high risk for nephron loss under adverse clinical conditions. Renal damage potentially collides with postnatal nephrogenesis. Recent animal studies suggest that nephron loss within this vulnerable phase leads to renal damage later in life. Nephrogenic pathways are commonly reactivated after kidney injury supporting renal regeneration. We hypothesized that nephron loss during nephrogenesis affects renal development, which, in turn, impairs tissue repair after secondary injury. Neonates prior to 36 wk of gestation show an active nephrogenesis. In rats, nephrogenesis is ongoing until day 10 after birth. Mimicking the situation of severe nephron loss during nephrogenesis, male pups were uninephrectomized at day 1 of life (UNXd1). A second group of males was uninephrectomized at postnatal day 14 (UNXd14), after terminated nephrogenesis. Agematched controls were sham operated. Three days after uninephrectomy transcriptional changes in the right kidney were analyzed by RNA-sequencing, followed by functional pathway analysis. In UNXd1, 1,182 genes were differentially regulated, but only 143 genes showed a regulation both in UNXd1 and UNXd14. The functional groups “renal development” and “kidney injury” were among the most differentially regulated groups and revealed distinctive alterations. Reduced expression of candidate genes concerning renal development (Bmp7, Gdnf, Pdgf-B, Wt1) and injury (nephrin, podocin, Tgf-b 1) were detected. The downregulation of Bmp7 and Gdnf persisted until day 28. In UNXd14, Six2 was upregulated and Pax2 was downregulated. We conclude that nephron loss during nephrogenesis affects renal development and induces a specific regulation of genes that might hinder tissue repair after secondary kidney injury.
CRIS-Team Scopus Importer:2021-12-17
Keywords: Neonatal nephron loss; Neonatal uninephrectomy; Nephrogenesis; Renal regeneration; RNA-sequencing